2016
DOI: 10.5539/elt.v9n4p106
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Act and Frequency of Plagiarism between Technical and Non-Technical Programme Undergraduates

Abstract: Concerned with intellectual theft, we decided to examine intellectual theft among undergraduates at a higher education institution. The aim of this study was to compare the act and frequency of plagiarism, particularly between programmes, gender, year of study and academic performance. This study adopted the quantitative approach, using a questionnaire to gather the students' background information and the general practice of intellectual theft. It was administered to 120 students. For the purpose of this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Meade (1992) revealed that among business, engineering, science and humanities faculties of 31 US universities the first two ranked top (87% and 74% of the students respectively) as the students admitted they have plagiarized at least once throughout their university life. These findings were confirmed by BavaHarji et al (2016) who also found out that plagiarism is more prevalent among students in technical rather than non-technical fields. However, students who are predominantly in the threat category and who might resort to plagiarism are ESL students as they are often involved in foreign language writing and they do not have native proficiency in it.…”
Section: Literature Reviewsupporting
confidence: 52%
See 2 more Smart Citations
“…Meade (1992) revealed that among business, engineering, science and humanities faculties of 31 US universities the first two ranked top (87% and 74% of the students respectively) as the students admitted they have plagiarized at least once throughout their university life. These findings were confirmed by BavaHarji et al (2016) who also found out that plagiarism is more prevalent among students in technical rather than non-technical fields. However, students who are predominantly in the threat category and who might resort to plagiarism are ESL students as they are often involved in foreign language writing and they do not have native proficiency in it.…”
Section: Literature Reviewsupporting
confidence: 52%
“…In this light, research on English as a Medium of Instruction students and the students of other majors such as ELT might provide different results. Studies on age difference (BavaHarji et al, 2016;Straw, 2002) found that younger students cheat more often than older and mature students, which partly contradicts the conclusion made in the study of Brown (1995) which stated that undergraduate and graduate students 'show similar frequencies of unethical behavior'. Research on the correlation between academic ability and plagiarism has also brought conflicting results.…”
Section: Literature Reviewmentioning
confidence: 93%
See 1 more Smart Citation
“…students, which indicates the educational level of the students may exert an influence on their academic dishonesty. More recently, the findings of BavaHarji et al (2016) supported the idea that educational level can be a determining factor in committing plagiarism. Also, Yang's (2014) study revealed that students of different genders and educational levels displayed different understandings of plagiarism.…”
Section: Literature Reviewmentioning
confidence: 78%
“…As can conspicuously be observed, previous research has yielded conflicting results with regard to the role of gender and educational level in academic dishonesty. Although results of some studies indicate that there exists a relationship between students' gender and their ethical behavior (Ameen, Guffey & McMillan, 1996) with most of the studies finding greater prevalence of plagiarism among male university students as compared to their female counterparts (Athanasou & Olasehinde, 2002;BavaHarji et al, 2016;Becker & Ulstad, 2007;Brunell, Staats, Barden & Hupp, 2011;Egan, 2008;Lin & Wen, 2007;Straw, 2002), in the context of Iran, Ahmadi (2014) found no noticeable role of gender in engaging in plagiarism by university students. Nevertheless, regarding the educational level, he found that B.A.…”
Section: Literature Reviewmentioning
confidence: 99%